A cross-sectional study on preponderance of stress and depression among engineering students and their association with various recent factors - Lakshmi Venkata S. Kutikuppala; Santhi Vadugu; Mohammed A Salaam; S V Venugopal Raju (Journal of Dr. NTR University of Health Sciences, 2020)
Background: Stress actually means body's psychological perception of pressure and its response to that pressure, involving multiple factors. The factors may be either external or internal/physical or biological. Stress-management is one of the most prevalent and popular topic of the latest times. Stress is mostly associated and leading to depression in the present juncture. Aims: The main objective of this study is to evaluate and elicit the levels of stress and depression in association with various recent factors accounting and resulting in them. Prevalence of stress and depression in relation to factors such as body mass index (BMI), social feeling, gastric problems, appetite, hair fall can also be assessed by this study. Materials and Methods: 298 engineering students of an engineering college were requested to answer up the analysis sheet comprising of Beck's Depression Inventory (BDI), Perceived Stress Scale (PSS) and other criteria comprising some selected factors adding to stress and depression. Analysis sheets were assessed, results were obtained and statistically analysed by GraphPad InStat Software. Results: The results of the present study indicate that majority of the students are having moderate and higher levels of stress, and no depression. Most of the people felt the higher levels of stress during the period of examinations. Conclusions: The students studying first year felt more stressed, which could be due to their recent entry into the course. Female students are more prone to these stressors and depressors. Juniors were more stressed when compared to senior students.